2015
DOI: 10.1093/abbs/gmv097
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal extension of calmodulin-like 3 protein from <italic>Oryza sativa</italic> L.: interaction with a high mobility group target protein

Abstract: A large number of calmodulin-like (CML) proteins are present in plants, but there is little detailed information on the functions of these proteins in rice (Oryza sativa L.). Here, the CML3 protein from rice (OsCML3) and its truncated form lacking the C-terminal extension (OsCML3m) were found to exhibit a Ca 2+ -binding property and subsequent conformational change, but the ability to bind the CaM kinase II peptide was only observed for OsCML3m. Changes in their secondary structure upon Ca 2+ -binding measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…It is well-recognized that calcium mediated signaling is important for plant responses to a wide variety of stresses including pathogen attack (Dodd et al, 2010;Batistic et al, 2012;DeFalco et al, 2010;Lecourieux et al, 2006). A large number of CaM and CaM-like (CML) proteins have been identi ed in rice genome (Boonburapong and Buaboocha 2007;Chinpongpanich et al, 2015). However, a scanty of reports is available for rice CBPs (Zhang et al, 2012;Shin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It is well-recognized that calcium mediated signaling is important for plant responses to a wide variety of stresses including pathogen attack (Dodd et al, 2010;Batistic et al, 2012;DeFalco et al, 2010;Lecourieux et al, 2006). A large number of CaM and CaM-like (CML) proteins have been identi ed in rice genome (Boonburapong and Buaboocha 2007;Chinpongpanich et al, 2015). However, a scanty of reports is available for rice CBPs (Zhang et al, 2012;Shin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Primary screening was carried out using the propagated library according to Chinpongpanich et al [ 119 ]. The 600-μl aliquots of XL1-Bule MRF2 cell suspension were mixed with the equivalent of 25,000 pfu of the amplified library and incubated at 37 °C for 15 min before plating as top agar with the addition of IPTG onto an LB agar plate.…”
Section: Methodsmentioning
confidence: 99%
“…OsHMGB is an OsCML3 target protein, and binds to DNA within the nucleus to regulate intracellular Ca 2+ (Aumnart et al, 2015). Several studies have shown that HMGB proteins are localized to the nucleus, are able to bind to specific DNA structures, and are involved in a variety of important biological processes (Grasser et al, 2007;Kang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%